J Nutr Food Sci 2019
DOI: 10.35248/2155-9600.19.9.760
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Glycosides Improve Motor Performance and Muscle Weight in Adult Mice

Abstract: Male C57BL/6J (B6) mice aged 24 weeks were provided two concentrations (1.5 or 3.0 g/L) of quercetin glycosides (QG) in drinking water over the subsequent 24 weeks. The objective was to determine if QG could improve motor function during early stages of aging. No sustained significant differences in body composition or food intake were noted to confirm the safety of QG treatment. Treated mice had significantly improved performance in grip strength and rotarod tests but not in treadmill performance. The functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, quercetin decreased the 3D-clinorotation-induced expression of atrogin-1 and MuRF-1 via the dephosphorylation of ERK [ 60 ], which is indicative of its efficacy in disuse muscle atrophy. Interestingly, long-term (24 weeks) oral treatment with quercetin glycoside effectively improved motor performance and increased muscle (quadratus femoris, gastrocnemius, tibialis anterior, and soleus) mass during the early stages of aging [ 104 ]. The stimulation of mitochondrial biogenesis by quercetin was also reported in a mouse experiment.…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…Furthermore, quercetin decreased the 3D-clinorotation-induced expression of atrogin-1 and MuRF-1 via the dephosphorylation of ERK [ 60 ], which is indicative of its efficacy in disuse muscle atrophy. Interestingly, long-term (24 weeks) oral treatment with quercetin glycoside effectively improved motor performance and increased muscle (quadratus femoris, gastrocnemius, tibialis anterior, and soleus) mass during the early stages of aging [ 104 ]. The stimulation of mitochondrial biogenesis by quercetin was also reported in a mouse experiment.…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…Apigenin reduced oxidative stress and inhibited hyperactive autophagy and apoptosis, alleviating age-related skeletal muscle atrophy in rats [ 77 , 78 ]. Kanzaki et al [ 79 ] reported that quercetin glycosides increased the wet weights of the quadratus femoris, gastrocnemius, tibialis anterior and soleus muscles in mice. While in the tibialis anterior and soleus muscles of rats, ferulic acid increased the production of mechano-growth factor and the antioxidant enzymes [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased wet weights of a particular group of muscles (quadratus femoris, gastrocnemius, tibialis anterior, and soleus) in the treated mice's muscular morphology demonstrated functional benefits. Hence, the long-term oral administration of QG during the early stages of aging can safely and effectively enhance certain aspects of motor performance and increase muscle mass [172].…”
Section: Antioxidantsmentioning
confidence: 99%